Pemahaman Kebahagiaan oleh Remaja Broken Home - Siti Khusnul Faizah (Taqorrub: Jurnal Bimbingan Konseling dan Dakwah, 2022)
Abstract Happiness is the expectation for every person including teenager. Study explaining that a broken home is a condition when the family is no longer intact. Family disorganization can be due to divorce, the death of one of the parents or problems that are not resolved properly. It could even be because of a third person in household matters, such as parents, in-laws, or the presence of another ideal woman or man. However, parental divorce may have impact on teenagers’ happiness. The aim of this study is to know happiness in teenager whose parents divorced. Data for this research were obtained using qualitative method with case study design. Subject was selected using purposive sampling technique. The respondent was a male teenager with divorced parents. Data collection was carried out through interview. The results showed that the respondent had three aspects of happiness are life is pleasant, meaningful, and engaging.